Seed morphoanatomy may confer restraints against the germination of Pouteria glomerata (Sapotaceae) in a Neotropical wetland - Lima, Liana Baptista de; Franco, Ana Paula Sales de Araujo; Scremin-Dias, Edna; Soares, Vanessa Couto; Arruda, Rosani do Carmo de Oliveira; Damasceno Junior, Geraldo Alves (Acta scientiarum. Biological sciences, 2025)
The tree-shrub species Pouteria glomerata (Miq.) Radlk. (Sapotaceae) occurs in periodically flooded areas marked by periods of drought. It has the potential for use in the ecological restoration of riparian forests; however, seed germination strategies were not fully understood. In this study, we aimed to evaluate the morphology, anatomy, and physiological aspects of the seed to identify possible factors related to low germination. The morphoanatomical seed analysis was assessed according to the routine procedures. For physiological assessment, seed germination was estimated under different conditions; seeds were scarified and soaked in water to overcome dormancy. Seeds store starch, lipids, and proteins, and are covered by a hard and thick seed coat. The embryo was underdeveloped consisting of a mass of meristematic cells. Numerous laticifers and phenolic idioblasts were found, mostly on the periphery of the cotyledons. Germination was hypogeal and the seedling was cryptocotylar type. The treatments to overcome seed dormancy were not efficient to break dormancy. The morphoanatomical analysis suggested that the dormancy of P. glomerata seeds may be related to an impermeable seed coat and undifferentiated or immature embryo indicating a morphophysiological dormancy.